Study of Hypervelocity Projectile Impact on Thick Metal Plates. (10th January 2016) - Roy, Shawoon K.; Trabia, Mohamed; O'Toole, Brendan; Hixson, Robert; Becker, Steven; Pena, Michael; Jennings, Richard; Somasoundaram, Deepak; Matthes, Melissa; Daykin, Edward; Machorro, Eric
Abstract : Hypervelocity impacts generate extreme pressure and shock waves in impacted targets that undergo severe localized deformation within a few microseconds. These impact experiments pose unique challenges in terms of obtaining accurate measurements. Similarly, simulating these experiments is not straightforward. This study proposed an approach to experimentally measure the velocity of the back surface of an A36 steel plate impacted by a projectile. All experiments used a combination of a two-stage light-gas gun and the photonic Doppler velocimetry (PDV) technique. The experimental data were used to benchmark and verify computational studies. Two different finite-element methods were used to simulate the experiments: Lagrangian-based smooth particle hydrodynamics (SPH) and Eulerian-based hydrocode. Both codes used the Johnson-Cook material model and the Mie-Grüneisen equation of state. Experiments and simulations were compared based on the physical damage area and the back surface velocity. The results of this study showed that the proposed simulation approaches could be used to reduce the need for expensive experiments.